2002
DOI: 10.1128/iai.70.2.787-793.2002
|View full text |Cite
|
Sign up to set email alerts
|

Phase Variation ofCampylobacter jejuni81-176 Lipooligosaccharide Affects Ganglioside Mimicry and Invasiveness In Vitro

Abstract: The outer cores of the lipooligosaccharides (LOS) of many strains of Campylobacter jejuni mimic human gangliosides in structure. A population of cells of C. jejuni strain 81-176 produced a mixture of LOS cores which consisted primarily of structures mimicking GM 2 and GM 3 gangliosides, with minor amounts of structures mimicking GD 1b and GD 2 . Genetic analyses of genes involved in the biosynthesis of the outer core of C. jejuni 81-176 revealed the presence of a homopolymeric tract of G residues within a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
214
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(229 citation statements)
references
References 36 publications
12
214
3
Order By: Relevance
“…Further, a recent study by Keo et al established that capsule expression was essential for Campylobacter resistance to human serum [114], though, in contrast to earlier reports [41,115], they did not find any essential contribution of sialylated LOS to serum resistance [114]. Therefore, the actual involvement of LOS in serum resistance is still under discussion.…”
Section: Serum Resistance and The Immune Responsecontrasting
confidence: 41%
“…Further, a recent study by Keo et al established that capsule expression was essential for Campylobacter resistance to human serum [114], though, in contrast to earlier reports [41,115], they did not find any essential contribution of sialylated LOS to serum resistance [114]. Therefore, the actual involvement of LOS in serum resistance is still under discussion.…”
Section: Serum Resistance and The Immune Responsecontrasting
confidence: 41%
“…C. jejuni, including the Miller-Fisher syndrome-associated serotypes HS:2 and HS:23, had GT1a-like and GQ1b-like oligosaccharides (59). A population of cells of C. jejuni strain 81-176 produced a mixture of LPS cores that consisted primarily of structures mimicking GM2 and GM3 gangliosides, with significantly fewer structures mimicking GD1b and GD2 (29). Anti-GQ1b IgG antibody was detected in most Miller-Fisher patients infected with C. jejuni or Haemophilus influenzae.…”
Section: Oligosaccharides Of Lpss That Mimic Ganglioside Structuresmentioning
confidence: 99%
“…In this regard, Linton et al (49) have reported that the wlaN gene product, which encodes a ␤-1,3-galactosyltransferase, is responsible for converting the GM2-like LOS structure to a GM1-like structure. The LPS of C. jejuni strain 81-176 expresses mainly a mixture of LPS cores containing GM2 and GM3 gangliosides (29). Genetic analyses of genes involved in the biosynthesis of the outer core of this strain revealed the presence of a homopolymeric tract of G residues within a gene encoding CgtA.…”
Section: Genetic Variability Of Campylobacter Jejuni and Its Relationmentioning
confidence: 99%
“…Several virulence factors contribute to the pathogenicity of C. jejuni, including the flagella that confer motility and are important for colonization (10,11), the glycosylation of proteins that allows antigen protection/masking (12,13), and surface glycolipids such as the lipooligosaccharide (14), and the capsule (15) that provide resistance to a wide array of innate immune defenses (16). The capsule is required for diarrheal disease and colonization in animal models of infection, as well as adherence, invasion, and serum resistance in human infections (17).…”
mentioning
confidence: 99%